Uplift at lithospheric swells-II: is the Cape Verde mid-plate swell supported by a lithosphere of varying mechanical strength? - Wilson, D; Peirce, C; Watts, A; Grevemeyer, I (2013)
The Cape Verde mid-plate swell is the largest amplitude oceanic mid-plate swell on Earth at ~1800 km in diameter, with a crest ~2.2 km high, and long-wavelength positive geoid, gravity and heat flow anomalies of 8 m, 30 mGal and 10-15 mW m-2, respectively. These characteristics and its location on the slow moving-to-stationary African Plate, which concentrates the volcanism and associated geophysical anomalies within a relatively small areal extent, makes it an ideal location to test various proposed mechanisms for swell support. Wide-angle seismic refraction data have been acquired along a ~474 km profile extending north-south from the swell crest. In this paper, the 2-D velocity-depth crustal model derived from forward modelling of phase traveltime picks is tested using two independent inversion approaches. The final crustal velocity-depth model derived from the combined modelling, shows no evidence for widespread thickened crust or for lower crustal velocities exceeding 7.3 km s, -1 that are indicative of undercrustal magmatic material. Using the final velocity-depth model to constrain the crust for 3-D 'whole plate' lithospheric flexure modelling of island loading alone, we showthat the lithosphere of the CapeVerde region appears stronger than expected for its age. Regional-scale modelling suggests that the majority of the swell height is supported by dynamic upwelling within the asthenosphere coupled with, but to a lesser degree, the effect of a region of low density in the deeper lithosphere, originating most likely from conductive reheating of the overlying plate due to its slow-to-stationary motion. When this regional upward-acting buoyancy force is considered in the context of the shorterwavelength flexure associated with island loading, modelling suggests that the apparent high plate strength is a consequence of, in effect, a regional unbending of a lithosphere that has a long-term strength typical for its age.© The Authors 2013. Published by Oxford University Press on behalf of The Royal Astronomical Society.